ANALISIS SEMIOTIKA PUISI â€œSELAMAT TINGGALâ€ KARYA CHAIRIL ANWAR - Mulyati, Lia (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
Chairil anwar's "Selamat Tinggal" poem has elements of a beautiful sound produced in the reading, and Chairil Anwar's poem is also full of figurative language that is typical of Chairil Anwar. It is related to matter of depth and retention of figurative language that is used to be unique and interesting for research. A goal that researchers want to get from the writing is to analyze and also know the meaning contained in the poem "Selamat Tinggalâ€. The method chosen for poetry study "Selamat TInggal" uses qualitative research methods that examine writing based on the content of studied literary poems. Moreover, the poem is analyzed using a semiotic approach that nudged the subject to the sassurue theory of the development of the linguistic science. The result of the analysis of the poem "Selamat Tinggal" using this semiotic approach resulted in three aspects of it; Symbol, icon and index.